Spór o koncepcje pedagogiki ogólnej - Leppert, Roman (Studia Edukacyjne, 2025)
Taking the common meanings of the term “concept” as a starting point, the author analyzes the concepts of general pedagogy that emerged in the last decade of the 20th century and then considers the consequences of their simultaneous co-occurrence. In the second part, the subject of the analysis is one of the concepts that assigns general pedagogy a privileged position among other pedagogical subdisciplines.